Persepsi Masyarakat Terhadap Pergaulan Bebas Masa Mominango di Bolangitang Barat, Bolaang Mangondow Utara - Djamada, Mayawi; Ayu Purnama, Andi Oktami Dewi Artha; Husnan, Moh. Ihsan; Ibrahim, Muhammad (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2024)
This research examines people's perceptions of promiscuity during the Mominango period, which is the first step to getting married. The Mominango period is a period of introduction to the prospective bride and groom as they move toward marriage and this is also a way for both parties to get to know each other more closely. During the Mominango period, there are things that each couple must pay attention to regarding social etiquette during the Mominango period. This research uses a qualitative approach to identifying and analyzing with interpretation techniques in looking at local community perceptions. The data required for this research was collected through a process of observation, in-depth interviews, literature, and documentation. This research aims to find out how society perceived free association during the Mominango period in West Bolangitang District. Based on the results of this research, shows that the Mominango procession in West Bolangitang District is where the men come to the women by conveying their aims and objectives to simultaneously discuss the dowry and matters related to the custom, but after the procession there is a form of free association which is influenced by factors environmental factors, lack of religious insight and low education factors which in turn gave rise to local community perceptions regarding promiscuity during the Mominango period which showed positive and negative perceptions from the community.